2023
DOI: 10.1021/acs.inorgchem.2c03817
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Intermediate Valence Behavior in the Zintl Compound Yb14ZnSb11 by Incorporation of RE3+ [Yb14–xRExZnSb11 (0.2 ≤ x ≤ 0.7), RE = Sc, Y, La, Lu and Gd]

Abstract: The solid solutions of Yb 14−x RE x ZnSb 11 (RE = Sc, Y, La, Lu, and Gd; 0.2 ≤ x ≤ 0.7) were prepared to probe the intermediate valency of Yb in Yb 14 ZnSb 11 . The substitution of Yb with RE 3+ elements should reduce or remove the intermediate valency of the remaining Yb ions. Large crystals are grown from Sn-flux, and the structure and magnetic susceptibility are presented. All compounds crystallize in the Ca 14 AlSb 11 structure type and the RE 3+ ions show Yb site substitution preferences that correlate wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Because the crystal structure does not have a site available for the single Yb 3+ , intermediate valency of Yb exists, and an average valency of 2.07 for all 14 Yb atoms provides the precise accounting. 6 Studies on the magnetism within this system have shown that Yb 14 ZnSb 11 exhibits a fluxional valency with Yb 2+/3+ , in which the amount of Yb 3+ within the system decreases with temperatures. 7 This deviation from the ideal zintl formulism in its lowest energy state leads to the system being electron deficient and heavily doped p-type (∼1 × 10 21 h + cm –3 ).…”
Section: Introductionmentioning
confidence: 91%
See 4 more Smart Citations
“…Because the crystal structure does not have a site available for the single Yb 3+ , intermediate valency of Yb exists, and an average valency of 2.07 for all 14 Yb atoms provides the precise accounting. 6 Studies on the magnetism within this system have shown that Yb 14 ZnSb 11 exhibits a fluxional valency with Yb 2+/3+ , in which the amount of Yb 3+ within the system decreases with temperatures. 7 This deviation from the ideal zintl formulism in its lowest energy state leads to the system being electron deficient and heavily doped p-type (∼1 × 10 21 h + cm –3 ).…”
Section: Introductionmentioning
confidence: 91%
“…The effect of Lu-substitution in Yb 14 ZnSb 11 is in contrast to that observed for Yb 14 MnSb 11 and is attributed to differences in the Yb valency. 6,10 The introduction of Lu into the system helped stabilize the YbSb phase upon oxidation; however, it did not negate the formation and subsequent melting of YbSb 2 , which proves to be problematic for forming…”
Section: ■ Conclusionmentioning
confidence: 99%
See 3 more Smart Citations